MARKETING AND INNOVATION IN THE ROMANIAN WINE MARKET - Maria Magdalena TUREK RAHOVEANU; Adrian TUREK RAHOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present research is focused on the link between entrepreneurship and rural economic growth in the direction and intensity of the net influence of farmers' entrepreneurial activities on rural economic development in Romania. This research delves into land use for grape production, a key element in Romania's wine processing industry. It examines the dynamics between consumption, production, and import in the wine market, noting in particular the increase in imports after Romania accedes to the European Union. In addition, it considers the impact of viticulture on land use amid food competition concerns. The study aims to elucidate the relationships between wine production, import, and consumption and assesses the capacity of domestic production to meet consumption demands. Using regression analysis of data on wine consumption, production, and import, the research uncovers significant findings. It reveals that a one-unit increase in wine consumption correlates with a 0.13-unit increase in both wine production and imports. This study contributes to a deeper understanding of the interaction between wine consumption, production, and import, helping predictive modeling and identifying sustainable entrepreneurial paths in the grape processing sector in Romania, given the considerable wine production potential.